Antioxidant Activity of Flavonoids and Phenolic Acids from Dodonaea angustifolia Flower: HPLC Profile and PASS Prediction - Fekade Beshah Tessema; Yilma Hunde Gonfa; Tilahun Belayneh Asfaw; Mesfin Getachew Tadesse; Rakesh Kumar Bachheti (Journal of Chemistry)
Background. Dodonaea angustifolia is a known medicinal plant across East Arica. The flower of D. angustifolia is not well investigated in terms of phytochemistry and biological activities. This study aims to investigate the presence of flavonoids and phenolic acids in the flower of D. angustifolia and its antioxidant activity. Methods. Preliminary phytochemical screening was carried out using the standard protocols. Antioxidant activity evaluation using DPPH assay and total phenol content (TPC) and total flavonoid content (TFC) determinations in the flower extract were compared with the values of the leaf extract. UHPLC-DAD analysis was managed to develop the profile of the flower extract. Prediction of biological activity spectra for substances (PASS) was done using an online server for antioxidant and related activities. Results. Preliminary phytochemical screening and TPC and TFC values confirmed the presence of flavonoids and phenolic acids. From the HPLC analysis of flavonoids, quercetin, myricetin, rutin, and phenolic acids such as chlorogenic acid, gallic acid, and syringic acid were detected and quantified. The biological activity spectrum was predicted for the detected and quantified polyphenols. Conclusions. D. angustifolia flower is a rich source of flavonoids and phenolic acids, which are extractable and can be checked for further biological activity. It was possible to identify and quantify phenolic compounds through HPLC analysis in the methanol extract of D. angustifolia flower. The PASS biological activity prediction results showed that there were stronger antioxidant activities for the identified flavonoids. Future work will emphasize the isolation and characterization of active principles responsible for bioactivity.